ISLAMIC GREEN HOUSING DESIGN (CASE STUDY: “KHARISMA RESIDENCE” IN GARUT REGENCY, WEST JAVA PROVINCE) - Ida Munfarida (IST AKPRIND Yogyakarta, 2018)
The increasing of population is positively correlated with the human settlement requirement, especially in Garut Regency which is currently developing. Law of the Republic of Indonesia No. 32/2009 aims to create environmentally sustainable development, this is according to QS. Al A’Raf : 56. In order to implement sustainable housing, it is necessary to build Islamic Green Housing that applies sustainable development based on Islamic values. This study designed Islamic Green Housing according to Islamic values and sustainable development. The objective of the research was to design “KHARISMA RESIDENCE” in Garut Regency as Islamic Green Housing. The study was conducted using quantitative and descriptive analysis. Quantitative analysis aims to calculate land use, water consumption and solid waste concentration. Descriptive analysis explains sustainability strategy. Based on the calculation of land use, Basic Structural Coefficient (KDB) is 70% consist of housing building, mosque, and security office. Green Base Coefficient (KDH) is 30%. Wastewaters are consisting of grey water and black water. Grey water can be collected in an on-site system. Meanwhile black water can be treated on composting toilet. Solid-waste management is according to mandate of MUI No. 47/2014 about Waste Management to Prevent Environmental Damage. The community can play a role by improving the air quality in the housing by providing green open space is about 30%. The reduction of wastewater by more efficient water use according to the teachings of Rasulullah SAW, with properly managed of wastewater and solid waste, and green open space existence can produce significant environmental advantages to the community.